2023
DOI: 10.1007/s00464-023-10169-9
|View full text |Cite
|
Sign up to set email alerts
|

A proposed difficulty grading system for laparoscopic bile duct exploration: benefits to clinical practice, training and research

Abstract: Background A gap remains between the mounting evidence for single session management of bile duct stones and the adoption of this approach. Laparoscopic bile duct exploration (LBDE) is limited by the scarcity of training opportunities and adequate equipment and by the perception that the technique requires a high skill-set. The aim of this study was to create a new classification of difficulty based on operative characteristics and to stratify postoperative outcomes of easy vs. difficult LBDE irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Also, 17% of LCBDE cases were converted to open CBDE in patients who underwent previous biliary tract surgery, while intraoperative blood loss, hospital stay, and time to oral diet were significant better in LCBDE than in open CBDE[ 57 ]. The study on grading the difficulty of CBDE, Nassar et al [ 58 ] found that difficult cases often present emergently, with symptoms like obstructive jaundice and prior sphincterotomy. Easy cases typically undergo TC exploration, whereas difficult cases were more likely to undergo TD exploration.…”
Section: Difficult Lcbdementioning
confidence: 99%
See 1 more Smart Citation
“…Also, 17% of LCBDE cases were converted to open CBDE in patients who underwent previous biliary tract surgery, while intraoperative blood loss, hospital stay, and time to oral diet were significant better in LCBDE than in open CBDE[ 57 ]. The study on grading the difficulty of CBDE, Nassar et al [ 58 ] found that difficult cases often present emergently, with symptoms like obstructive jaundice and prior sphincterotomy. Easy cases typically undergo TC exploration, whereas difficult cases were more likely to undergo TD exploration.…”
Section: Difficult Lcbdementioning
confidence: 99%
“…Choledochoscopy was more commonly utilized in difficult cases. As difficulty increased, there was a rise in the use of biliary drains, open conversions, operative time, complications, hospital stay, readmissions, and retained stones[ 58 ].…”
Section: Difficult Lcbdementioning
confidence: 99%